IN SILICO DOCKING ROSELLE (HIBISCUS SABDARIFFA L.) CALYCES FLAVONOIDS AS ANTIMALARIAL AGAINST PLASMEPSIN 1 AND PLASMEPSIN 2 - Nerdy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Study the in silico plasmepsin 1 and plasmepsin 2 inhibition antimalarial effects of roselle (Hibiscus sabdariffa L.) calyces flavonoids compared to artemisinin as astandard compound for antimalarial to inhibit plasmepsin 1 and plasmepsin 2. Methods: Partition coefficient was predicted by the ChemDraw Ultra. In silico molecular docking was done by Protein-Ligand ANT System. Visualization was done by Yet Another Scientific Artificial Reality Application. Connector for Windows operation system to Linux operation system was done by Co Pendrive Linux. Three dimensions enzyme structure models used in this research were plasmepsin 1 and plasmepsin 2 with the protein data bank code 3QS1 and 1LEE obtained through the website http://www.rcsb.org/pdb. Two dimensions and three dimensions conformation model of compounds were generated by Marvin Sketch. Results: Partition coefficient of roselle calyces flavonoids quercetin, gossypetin, hibiscetin, and artemisinin, respectively, were 0.58, â€“0.44, â€“0.43, and 3.17. Higher partition coefficient means easier to penetrate into the cell. Docking score of roselle calyces flavonoids quercetin, gossypetin, hibiscetin, and artemisinin to plasmepsin 1, respectively, were â€“70.1989, â€“70.9454, â€“70.5870, and â€“61.7685 to plasmepsin 2, respectively, were â€“73.8620, â€“76,0086, â€“78.8930, and â€“61.7437. Lower docking score means a better potential activity to protein enzyme. Conclusion: Roselle calyces flavonoids (quercetin, gossypetin, and hibiscetin) show the stronger activity than artemisinin to inhibit plasmepsin 1 and plasmepsin 2. Â